2010
DOI: 10.1523/jneurosci.0140-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Top-Down Task Context in Learning to Perceive Objects

Abstract: In high-level perceptual regions of the ventral visual pathway in humans, experience shapes the functional properties of the cortex: the fusiform face area responds most strongly to faces of familiar rather than unfamiliar races, and the visual word form area (VWFA) is tuned only to familiar orthographies. But are these regions affected only by the bottom-up stimulus information they receive during learning, or does the effect of perceptual experience depend on the way that stimulus information is used during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 60 publications
2
37
1
2
Order By: Relevance
“…The analyses further revealed interactions between task and stimulus type throughout this network, suggesting that its function is not fixed, but can be reorganized in response to task demands (Starrfelt & Gerlach, 2007; Song, Hu, Li, Li, & Liu, 2010; Xue et al, 2010; Wang et al, 2011). The form of this interaction was remarkably similar throughout fusiform, middle and inferior frontal gyri, such that activity was overall quite low, and not influenced by stimulus class in the symbol detection task, but strongly affected by stimulus class in the lexical decision task.…”
Section: Discussionmentioning
confidence: 95%
“…The analyses further revealed interactions between task and stimulus type throughout this network, suggesting that its function is not fixed, but can be reorganized in response to task demands (Starrfelt & Gerlach, 2007; Song, Hu, Li, Li, & Liu, 2010; Xue et al, 2010; Wang et al, 2011). The form of this interaction was remarkably similar throughout fusiform, middle and inferior frontal gyri, such that activity was overall quite low, and not influenced by stimulus class in the symbol detection task, but strongly affected by stimulus class in the lexical decision task.…”
Section: Discussionmentioning
confidence: 95%
“…Third, the large interindividual functional variability may arise from the functional plasticity of the brain through cortical competition. Previous studies on visual development (Golarai et al, 2007), expertise (Gauthier et al, 2003), and plasticity in sensory maps (Polley et al, 2006;Song et al, 2010) have revealed a displacement of map boundaries due to cortical competition. Thus, individual experiences in the early or even late years of development may significantly contribute to the interindividual variability of the FSRs.…”
Section: Sources Of Interindividual Variabilitymentioning
confidence: 95%
“…It is usually characterized by some degree of specificity to the trained stimulus attributes including stimulus location (e.g., Ball and Sekuler 1982;Karni and Sagi 1991;Poggio et al 1992;Ahissar et al 1998;Saffell and Matthews 2003;Jastorff et al 2006;Bi et al 2010), the recruitment of stimulus-specific cortical areas (e.g., Vaina et al 1998;Schwartz et al 2002;Furmanski et al 2004;Grossman et al 2004;Song et al 2010;Bi et al 2014;Frank et al 2014), as well as stability of acquired behavioral improvements over time (e.g., Ball and Sekuler 1987;Karni and Sagi 1993;Watanabe et al 2002;Bi et al 2014;Frank et al 2014). The study of perceptual learning has the potential to provide insights into neural correlates of learning more generally.…”
Section: Introductionmentioning
confidence: 99%
“…However, to confirm this a posteriori, we measured brain activity during performance of the learning task, relative to a control condition, for the first and last training sessions using functional MRI (fMRI). We predicted increased activity in the 4 regions of interest (ROIs) after behavioral training (see Vaina et al 1998;Schwartz et al 2002;Furmanski et al 2004;Grossman et al 2004;Kourtzi et al 2005;Yotsumoto et al 2008;Song et al 2010;Frank et al 2014).…”
Section: Introductionmentioning
confidence: 99%